The Comparative Analysis of Social Dialect of Minangkabaunese used by Employees and Labourers in Padang - Monalisa Febriani; Jufrizal Jufrizal (Universitas Negeri Padang, 2019)
Social dialect is a branch of dialectology discusses about different language used because of social socio-economic background and educational background. From those background differences, it turns out to cause linguistic phenomena in the use of language which is one of the symbols as a determinant of social status. Most researchers have studied about different language used due to social status that discussed the language variety, meanwhile in this research the different language used is discussed in three aspect such as different diction, different pronunciation and different suprasegmental (stress) between employees and labourers in Padang. The method used in this research is by provoking the informant to utter the words researcher intended by using interview guideline. The data are words that are explained in comparative description form. The result of this research is there are found 5 types of different diction, 3 types of different pronunciation with the same diction and 3 types of different stressed sound with the same diction used between employees and labourers in Padang.